2013
DOI: 10.1186/1472-6882-13-322
|View full text |Cite
|
Sign up to set email alerts
|

Ardipusilloside I induces apoptosis by regulating Bcl-2 family proteins in human mucoepidermoid carcinoma Mc3 cells

Abstract: BackgroundArdisia pusilla A. DC., family Myrsinaceae, is a traditional Chinese medicine named Jiu Jie Long with a variety of pharmacological functions including anti-cancer activities. In this study, we purified a natural triterpenoid saponin, ardipusilloside I, from Ardisia pusilla, and show that it exhibits inhibitory activities in human mucoepidermoid carcinoma Mc3 cells. We also investigated the underlying mechanisms of proliferation inhibition that ardipusilloside I exerts on Mc3 cells.MethodsMTT test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A recent study involving pigs also evaluated that Bcl-2 and Bax are important regulators of cell apoptosis induced by heat shock (Fan et al, 2017). Although the mechanism that Bcl-2 family regulates cell apoptosis is not now fully understood, it has been suggested that the regulation of apoptosis is mainly linked to mitochondrial dysfunction (Xu et al, 2013;Wang et al, 2017). A previous study (Rogério et al, 2006) has demonstrated that Bcl-2 is located on the outer membrane of mitochondria, whereas Bax is considered to be either on the mitochondrial outer membrane or in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving pigs also evaluated that Bcl-2 and Bax are important regulators of cell apoptosis induced by heat shock (Fan et al, 2017). Although the mechanism that Bcl-2 family regulates cell apoptosis is not now fully understood, it has been suggested that the regulation of apoptosis is mainly linked to mitochondrial dysfunction (Xu et al, 2013;Wang et al, 2017). A previous study (Rogério et al, 2006) has demonstrated that Bcl-2 is located on the outer membrane of mitochondria, whereas Bax is considered to be either on the mitochondrial outer membrane or in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Mucoepidermoid carcinoma (MEC), representing 40–52% of all major and minor salivary gland malignancies, is the most common malignancy of the salivary gland. 1 It shows morphological diversity even within a specific tumor type. 2 Although MEC sometimes exhibits slow growth resembling that of a benign lesion, this neoplasm can be highly aggressive with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis was measured using flow cytometry to quantify the levels of detectable phosphatidylserine on the outer membrane of apoptotic cells [ 8 ]. Aloe-emodin induces apoptosis of the cells was measured using an Annexin V- Fluorescein isothiocyanate (FITC)/ propidium iodide (PI) apoptosis detection kit (Solarbio life Sciences, Beijing, China) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%